Efektivitas google meet sebagai media komunikasi belajar online bagi mahasiswa Rantau di desa Hegarmanah kabupaten Sukabumi - Anjani, Nesya Salsabila Puti (Komunika: Journal of Communication Science and Islamic Dakwah, 2022)
This research is based on communication media as a means of communication for overseas students in Hegarmanah village, Sukabumi regency which is used during the pandemic during online learning, the media used is the Google Meet application. This study aims to determine the effectiveness of the Google Meet communication media as a means of online learning for overseas students in Hegarmanah village, Sukabumi regency. This study uses a qualitative descriptive method, with data collection using several techniques to obtain complete data including literature studies and interviews. The results of this study, namely the Google Meet communication media as a means of communication for students in Hegarmanah village, Sukabumi regency can be said to be quite effective. The internet network is one of the causes of quite effective communication which makes the delivery of learning and communication between lecturers and students not optimal. If the policy of increasing the renewal of the internet network is implemented, it will provide benefits for the realization of effective communication. Abstrak Penelitian ini berlatar belakang dari media komunikasi sebagai sarana komunikasi mahasiswa rantau di Desa Hegarmanah Kabupaten Sukabumi yang digunakan pada masa pandemi selama melakukan pembelajaran online, media yang digunakan yaitu aplikasi Google Meet. Penelitian ini bertujuan untuk mengetahui efektivitas media komunikasi Google Meet sebagai sarana pembelajaran online mahasiswa rantau di desa Hegarmanah kabupaten Sukabumi. Penelitian ini menggunakan metode deskriptif kualitatif, dengan pengumpulan data menggunakan beberapa teknik untuk memperoleh data yang lengkap diantaranya adalah studi literatur dan wawancara. Hasil penelitian ini yaitu media komunikasi Google Meet sebagai sarana komunikasi mahasiswa di desa Hegarmanah kabupaten Sukabumi dapat dikatakan cukup efektif. Jaringan internet menjadi salah satu penyebab komunikasi cukup efektif yang menjadikan penyampaian pembelajaran dan komunikasi antara dosen dan mahasiswa tidak maksimal. Jika kebijakan menambah pembaharuan jaringan internet diterapkan, maka akan memberikan manfaat terwujudnya komunikasi yang efektif.